(untitled) (Texas Journal of Medical Science, 2025)
The clinical efficacy and safety of riamilovir were assessed based on the results of a study of 150 patients in three compared groups, 50 patients in each. Patients received etiotropic antiviral therapy with riamilovir, 1 capsule (250 mg) 3 times a day for 5 days in the first group, in the second group patients received riamilovir in the “off label” regimen, 1 capsule (250 mg) 5 times a day for 5 days, and the third group consisted of 50 patients who received only pathogenetic treatment. The etiotropic antiviral drug riamilovir demonstrated clinical efficacy when used in both treatment regimens in patients with ARVI and a good safety profile